E-wallet: dominating future transaction method for generation Z in Malaysia - Chai, Lee Wen; Wong, Jamie Hui Kun; Low, Xiao Pei; Tan, Ying Xin (2022)
This research is intended to examine the factors influencing the adopt intention of E-wallet among Generation Z in Malaysia. Generation Z refers the generation who born from 1997 to 2012. Factors included in this research are taken references from the Unified Theory of Acceptance Use of Technology 2 (UTAUT2) theory, which include performance expectancy, effort expectancy, social influence, facilitating conditions, habit, and hedonic motivation. The target respondents for this research are Malaysian Generation Z who born between 1997 and 2005 and have experiences in using E-wallet. A total of 396 eligible responses had been collected and used in data analysis. Partial least squares structural equation modeling (PLS-SEM) was applied as the research methodology in this research using Smart PLS version 3.3.7, along with Outer loadings analysis, reliability test, discriminant validity test, and bootstrapping. From the findings, it showed that social influence, habit and hedonic motivation are significant towards adopt intention of E-wallets for Generation Z in Malaysia. On the other hand, performance expectancy, effort expectancy, and facilitating conditions are not significant in influencing the adopt intention of Generation Z. Discussions on relationship between variables as well as the implication of this research had also performed in the paper. In additions, some limitations and recommendations about this research are included to provide more comprehensive information to the readers.